Copistes et lecteurs du Dalā’il al-khayrāt dans le Maroc prémoderne (xviiie-xixe siècles) - Hiba Abid (Revue des Mondes Musulmans et de la Méditerranée)
In Morocco, devotional literature devoted to the Prophet was very prolific, particularly from the first half of the 8th/14th century and prefigured the success of the prayer book on the Prophet, Dalā’il al-Khayrāt created in the following century by Muḥammad b. Sulaymān al-Jazūlī (d. 869/1465). This Moroccan mystic, founder of the Jazūlite Sufi order played a crucial role in the religious life of Morocco by placing the prayer on the Prophet at the heart of Muslim spirituality. This article questions the practical manifestations of pre-modern Moroccan Sufism through the codicological study of the manuscripts of the Dalā’il produced in Morocco from the 12th/18th to the end of the 13th/19th centuries. How did the book come to mediate the Jazūliyya doctrine, from its circulation within the zāwiyas’ circles to its diffusion among the different layers of Moroccan society? What are the graphic and ornamental devices used by the actors of this transmission, i.e., the manuscripts’ makers, that ensure the reading, the memorization, and the interpretation of the text by its users? The paper also explores how the latter appropriated and personalized the text, beyond the doctrine.